2011
DOI: 10.1002/app.34669
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of polyphenylene sulfide/multiwalled carbon nanotube composites

Abstract: Polyphenylene sulphide (PPS)/multi-walled carbon nanotube (MWCNT) composites were prepared using a melt-blending procedure combining twin-screw extrusion with centrifugal premixing. A homogeneous dispersion of MWCNTs throughout the matrix was revealed by scanning electron microscopy for the nanocomposites with MWCNT contents ranging from 0.5 to 8.0 wt%. The mechanical properties of PPS were markedly enhanced by the incorporation of MWCNTs. Halpin-Tsai equations, modified with an efficiency factor, were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…The optimized fi lm was subsequently used as a transparent conductor (anode) in a fl exible and ITO-free organic photovoltaic (OPV) device, showing outstanding performances, (Figure 2 b) is thinner ( ≈ 50 nm) and covers the entire substrate. The dispersion in the diameter distribution of the larger nanotubes is also three times higher than that of the thinner nanotubes, as shown in Figure 2 c. [ 27 ] This discrepancy may lead to poorer assembly of carbon nanotubes at the liquid interface and thereby contribute to a nonuniform fi lm. Thus, small-diameter nanotubes and/or low diameter dispersion are crucial to the production of high-quality fi lms.…”
Section: Self-assembled Thin Films Of Carbon Nanotubes and Polyanilinementioning
confidence: 94%
“…The optimized fi lm was subsequently used as a transparent conductor (anode) in a fl exible and ITO-free organic photovoltaic (OPV) device, showing outstanding performances, (Figure 2 b) is thinner ( ≈ 50 nm) and covers the entire substrate. The dispersion in the diameter distribution of the larger nanotubes is also three times higher than that of the thinner nanotubes, as shown in Figure 2 c. [ 27 ] This discrepancy may lead to poorer assembly of carbon nanotubes at the liquid interface and thereby contribute to a nonuniform fi lm. Thus, small-diameter nanotubes and/or low diameter dispersion are crucial to the production of high-quality fi lms.…”
Section: Self-assembled Thin Films Of Carbon Nanotubes and Polyanilinementioning
confidence: 94%
“…They also show a uniquely high thermal conductivity of 2800-6000 W/ mK at room temperature [1,2] , which is greater than those of graphite and carbon fibers. It has been reported that CNT acts as an efficient nucleating agent on polymers, including polypropylene (PP) [3,4] , nylon [5,6] , poly(phenylene sulfide) (PPS) [7][8][9] , and polyolefins [10] , and accelerates the crystallization process. It has been observed that the crystallinity of polymer has a very important influence on the thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(phenylene sulfide) is an engineering thermoplastic material with outstanding comprehensive performance, exhibiting high mechanical strength, good thermal stability, chemical resistance, and excellent electrical properties [7,[16][17][18] . Khan et al [19] investigated the effects of microsized and nanosized carbon fillers respectively on the thermal and electrical properties of PPS-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications can be found on nanocomposites with many other polymers, such as ethylene-vinyl acetate copolymer [102], polyvinylidene fluoride [103], polyolefins [104], acrylonitrile-butadiene-styrene [105], polyphenylene sulfide [106], poly(ethylene terephthalate) (PET) [107], and many more. Even though interactions between polymers and nanotubes are quite different from the projected functionality in membranes, the polymer-nanotube conjunction is a basic starting point showing a glimpse of the potential of hybrid materials.…”
Section: The Use Of Nanotubes In Conjunction With Polymersmentioning
confidence: 99%